An analysis on the potential of solar photovoltaic power. Issue 10 (3rd October 2017) - Samu, Remember; Fahrioglu, Murat
ABSTRACT: In this present paper, the potential of solar photovoltaic power in Zimbabwe so as to cater for the rising energy demand is assessed. The main objective of this present study is to convert solar resources in 28 different locations scattered all over the country into electrical energy. This investment requires a capital cost of US$18, 952, 500 and a total land area of 51, 020 . The 10 MW grid-connected PV potential is feasible for all the chosen locations. Chegutu seems to be the most suitable and profitable site for the construction of the plant and Chiredzi location results in a minimum profit. From an environmental point of view and considering the expected output energy production, investments at Chegutu are highly preferable. The amount of carbon dioxide reduced annually and the cost of electricity are also outlined in this study in which a comparative analysis to the existing grid tariff will be made.